(untitled) (Confluenţe Bibliologice, 2021)
The article presents the results of the research on the efficiency of ensuring access to information by the USARB Scientific Library for its users during the COVID-19 pandemic and identifies the opinion of users regarding access to information in the SL USARB during a pandemic crisis. There are also analyzed the students’ answers to the questions from the online opinion poll "Access to information of SL USARB users during the pandemic crisis".